The Birth of Prophet Mu?ammad in the Qur’?n: A Critical Analysis of al-J??i?’s Thought in his Kit?b al-?ujja f? Tathb?t al-Nubuwwa (KEMANUSIAAN The Asian Journal of Humanities, 2018)
According to Islamic tradition, Prophet Mu?ammad was born in the Year of the Elephant, the year of Abraha’s unsuccessful expedition against Mecca. Relying on references made from the Qur’?nic text alone, not a single verse refers definitively to the event of the Prophet’s birth. However, some Muslim biographers have chosen s?rah al- F?l of the Qur’?n as the verse which carries an early sign of the Prophet’s emergence, while others attributed this chapter to the event of the Prophet’s birth. Al-J??i? was among them, and this notion was articulated in his Kit?b al-?ujja f? Tathb?t al-Nubuwwa, where he expressed his opinion on the exegesis of this chapter. Thus, the present study aims to explore the narrative of the Prophet’s birth, analyse the historical connection between the occurrence and s?rah al-F?l and examine hermeneutical responses of Muslim exegetes on the verse, especially al-J??i?. The study is qualitative in nature in which the researcher employed both critical and analytical approaches to the works of tafs?r and s?ra. Findings of this study assert that conviction and zeal to authenticate the story of the People of the Elephant seems to have influenced al-J??i? to adduce s?rah al-F?l as a solid basis of evidence of the whole truth of this narrative.